KOORDINASI DINAS PERHUBUNGAN DENGAN SATUAN POLISI PAMONG PRAJA DALAM MEMFUNGSIKAN PEDESTRIAN DI KOTA PEKANBARU - Winda Witami; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Pedestrian is a sidewalk that is destined for pedestrians to enjoy the feel of urban buildings and gardens City / District. In an urban context it is usually referred to as a special room for pedestrians that serves as a means of attainment which can protect from the danger coming from motor vehicles. The sidewalks in Pekanbaru have been transformed into two-wheeled parking spaces, where street vendors, billboards and so on. Several related agencies are responsible with this matter, such as the Office of Transportation with the Municipal Police Force Unit Pekanbaru. The purpose of this study is to find out how the coordination between relevant agencies in the functioning of pedestrian and to determine what factors affect the coordination between the two related agencies.This research was conducted to know the coordination between the Department of Transportation with the Civil Service Police Unit in Functioning Pedestrian in Pekanbaru City. Using the grand theory of Fayol, Koontz and O'Donnell, in which there are 4 indicators are: 1. Cooperation in harmony, 2. Knowing each task. 3. Good communication, 4. Meetings through meetings. This research uses qualitative descriptive method. The technique of collecting through observation, interview and documentation with key informant as source of information and technique of snowball as source of data validity.The result of the research stated that the coordination that has been done by the Transportation Agency with the Pekanbaru City Police Precinct Police Unit has not been optimally can be seen from 4 indicators namely communication, cooperation, division of tasks and meeting meetings conducted not only after the violation but must be done for supervisory control in the pedestrian . In addition, supporting facilities and infrastructure should be sufficient to create optimal performance between the two agencies. Facilities and infrastructure should also be supported by potential human resources (HR) so that everyone knows their duties and functions in order to avoid overlap in the execution of tasks. If all this goes well, then pedestrian will serve as a place for pedestrians.Keywords: Coordination, Pedestrian